Female Users’ Behavioral Intention to Purchase in Social Commerce through Social Networking Sites - Phyo Min Tun (Shirkah: Journal of Economics and Business, 2021)
The present study aims to discover the relationship among social influence, verbal influence, easiness, trust, enjoyment, and intention to purchase in social commerce (S-Commerce), particularly by female users of social networking sites (SNS). A total of 280 responses were collected from female SNS users through an online survey. The obtained data were further examined for normality, construct validity, reliability, and model fit, using Structural Equation Modeling (SEM) to test the hypotheses. This study confirmed that social influence had a significant effect on verbal influence and trust; meanwhile enjoyment was influenced by trust and easiness. The results also revealed that trust and enjoyment had a positive effect on intention to purchase products or services from social commerce by the female SNS users. Moreover, verbal influence provided an impact on trust and easiness; while the relationship between social influence and enjoyment, easiness, and trust was not significant. These results contribute to offering fruitful insights for sellers and vendors of social commerce in attracting and acquiring the attention of female customers; as a result, it leads to achieving higher profits and flourishing business activities in social commerce.